Do rock ao repente: identidades híbridas nas canções de Zé Ramalho no contexto da década de 1970 - Gomes, Jandynéa de Paula Carvalho (2012)
This dissertation has as object of study the songs composed by Zé Ramalho of Paraíba, during the 1970s. These songs were produced and recorded in the context of the rise of a group of musicians who moved from Northeast to the southeast of the country to try to make a living out of music, the "onda nordestina" which was attended by Zé Ramalho, Alceu Valença, Geraldo Azevedo, Ednardo, Belchior and Fagner. Starting from the concept of hybridization, proposed by the argentine anthropologist Néstor García Canclini, we intent to identify, through which artistic procedure (musical and poetic) Zé Ramalho, select and blend elements that were present in the context of the 1970s. We appeal to the ideas of researchers of popular music in Brazil that claim the ambiguous character of this object of study and defend the need to develop researches that dialogue with different disciplines and that include the parameters present in the song: the poetic and musical. Among these researchers, should be highlighted Wisnik José Miguel, José Leonardo de Moraes, Marcos Napolitano and Luiz Tatit. Linked to the discussion about popular music, we propose a more general about the categories of popular and national identity, elements of our historical culture, which lay roots in interpretations about Brazilian culture, based on theoretical ideas of the so-called Cultural Studies.